2014
DOI: 10.1210/en.2013-1639
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the Neural Circuitry Underlying Sexual Behavior to Chronic Adult Exposure to Oral Bisphenol A in Male Mice

Abstract: There are human reproduction concerns associated with extensive use of bisphenol A (BPA)-containing plastic and, in particular, the leaching of BPA into food and beverages. In this context, it remains unclear whether and how exposure to BPA interferes with the developmental organization and adult activation of male sexual behavior by testosterone. We evaluated the developmental and adult exposure to oral BPA at doses equivalent to the no-observed-adverse-effect-level (5 mg/kg body weight per day) and tolerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 47 publications
2
68
1
Order By: Relevance
“…Second-pregnancy dams were administered, by oral gavage, sesame oil (vehicle group) or sesame oil containing BPA (Sigma-Aldrich) at 5 mg/kg body weight per day (BPA-NOAEL group) or BPA at 0.050 mg/kg body weight per day (BPA-TDI group). Treatments were carried out each day from gestational day 15 until postnatal day 21 (Picot et al 2014). After weaning, female offspring were allowed to grow until analyses.…”
Section: Treatmentsmentioning
confidence: 99%
“…Second-pregnancy dams were administered, by oral gavage, sesame oil (vehicle group) or sesame oil containing BPA (Sigma-Aldrich) at 5 mg/kg body weight per day (BPA-NOAEL group) or BPA at 0.050 mg/kg body weight per day (BPA-TDI group). Treatments were carried out each day from gestational day 15 until postnatal day 21 (Picot et al 2014). After weaning, female offspring were allowed to grow until analyses.…”
Section: Treatmentsmentioning
confidence: 99%
“…Exposure to BPA for 2 weeks has no effect on male rats [66]. By contrast, longer periods of exposure of male mice to BPA increased the times to mounting, intromission and ejaculation, and decreased the numbers of intromissions and thrusts in both naïve and sexually experienced male mice [63]. Similar differences between short- and long-term exposures were observed for corncob bedding and derived tetrahydrofuran-diols [67, 68].…”
Section: Effects Of Edc On Sexual Behaviormentioning
confidence: 96%
“…Decatanzaro et al [61] observed only a fewer number of intromissions in animals exposed to BPA in a high-phytoestrogen diet. In addition, male mice exposed to BPA displayed less lordosis behavior than the vehicle group when gonadectomized and primed with E2 and progesterone, indicating a greater masculinization of behavior [63]. When given a choice between control and BPA-exposed partners, female mice preferred controls over BPA-exposed males [65].…”
Section: Effects Of Edc On Sexual Behaviormentioning
confidence: 99%
See 2 more Smart Citations